Identifikasi Trichoderma sp. dari Rizosfer Tanaman Kanonang (Chordia dichotoma. G. Forst) dan Karakteristik Pemacu Pertumbuhan serta Daya Antagonismenya Terhadap Fusarium oxysporum - Billy David Rawis; Dylan R. Pahlevi; Parluhutan Siahaan; Marina Singkoh; Agustina Tangapo (JURNAL BIOS LOGOS, 2024)
The use of biological control agents to inhibit the growth of pathogens in this case Fusarium in agricultural plants is very important in order to reduce the impact of environmental damage. Trichoderma sp. is a fungus that can be obtained from the rhizosphere of plants that can increase soil fertility and inhibit pathogenic fungi that cause damage to agricultural plants. The use of local isolates of antagonistic fungi in this case from the rhizosphere of the Kanonang plant gave results where the discovery of Trichoderma species that are able to control plant pathogens in this case Fusarium oxysporum through antagonism mechanisms such as inhibition, antibiosis and microparasitism. To find out the species of Trichoderma sp, it was continued with a molecular test using the ITS marker gene and the results of the test confirmed that the Trichoderma species in the rhizosphere of the Kanonang plant was the Trichoderma asperellum type. This type of Trichoderma also after being tested for its characteristics in stimulating growth gave positive results for both phosphate solvent and auxin producer (IAA) tests